Down-regulation of MCH II molecules by ubiquitination is required for the accumulation of CD206+ monocyte-derived DCs in lymph nodes. (October 2022) - Majdoubi, Abdelilah; Lee, Jun Seong; Balood, Mohammad; Talbot, Sébastien; Cheong, Cheolho; Thibodeau, Jacques
Abstract : Migratory DCs play a critical role in skin immunity. A subset of these cells infiltrate skin come from the extravasation of blood monocytes (P1) that continuously differentiate into an intermediate stage (P2) before becoming fully functional DCs (P3), which can migrate to skin draining lymph nodes (sdLNs). During their development into monocyte-derived DCs (moDCs), in parallel with the downregulation of Ly-6C, P1-P2-P3 progressively upregulate MHC class II molecules (MHCII) and the mannose receptor (CD206). Aim: To study the role of MHCII expression in the biology of migratory DCs. Methodology: We studied by flow cytometry the development and migration of skin moDCs using four transgenic mouse models expressing different MHCII levels. RESULTS: Using CD206 as a surrogate marker for MHCII to identify P1, P2 and P3, we found that variations in the levels of MHCII did not affect the development of skin moDCs. However, tempering with ubiquitination of I-A resulted in the over-expression of MHCII, a decrease in the expression of IRF4 and CCR7, and prevented migration of skin moDCs to sdLNs. Interestingly, mice overexpressing MHCII developed larger tumors in B16-mel-anoma model. However, a GM-CSF-producing B16 variant increased the expression of IRF4 in tumor moDCs and restored their migration to sdLNs. Conclusion: The data show that although not required for their development in the skin, the down-regulation of MHCII by ubiquitination is crucial for IRF4\CCR7 dependent migration of CD206+DCs to the sdLN in homeostasis and during inflammation.